Exploring the Lower Limit of Individual DNA-Encoded Library Molecules in Selection. (June 2020) - Chen, Qiuxia; Cheng, Xuemin; Zhang, Lifang; Li, Xianyang; Chen, Purui; Liu, Jian; Zhang, Lanjun; Wei, Hong; Li, Zhonghan; Dou, Dengfeng
DNA-encoded library (DEL) technology has been used as an ultra-high-throughput screening approach for hit identification of drug targets. This process is an affinity-based selection and requires incubation of DEL molecules with the target. Currently, in most reported cases, the input (i.e., the copy number) of individual DEL molecules varies from 10 5 to 10 7 . With the ever-increasing DEL size and screening cost, lowering the input of DEL molecules while maintaining an appropriate signal-to-noise ratio in a selection is of paramount importance. In this article, we varied the input of DEL ranging from 10 3 to 10 5 in selections with two different protein targets to explore the lower limit of DEL molecule input. The results could facilitate the optimization of the DEL selection process and reduce costs related to library consumption.